Projeto e análise: órtese de acionamento pneumático para recuperação de movimentos manuais - Barbosa, Flávia Aparecida Santos (Universidade Federal de São Carlos, 2021)
Currently in Brazil, several cases of patients who have suffered a stroke (cerebrovascular accident) are reported daily. One of the consequences of a stroke is the loss of movement on one side of the body. So that the patient can recover the lost movements, rehabilitation is necessary with constant monitoring of a multidisciplinary team. There is currently physical therapy equipment that aim to recover manual movements; however, they go from the principle that the hand original state is open. Given that in some cases the patient will have the closed hand as the original position, in which the muscles are contracted, and that the proposals already developed do not adequately address this situation, this work aims to study, analyze, and propose a prototype of device that meets this situation where the model presented will be actuated pneumatically. Due to the absence of similar equipment in the bibliography, a base geometry was elaborated to meet the proposed problem. Based on the proposed geometry and working principle, it was noted the need to use a hyperelastic material for the manufacture of the model. Due to that fact, materials found in the bibliography and that had already been used in previous works at UFSCar were used. After defining the geometry and material to be used, finite element simulations were performed to obtain the displacements that the device will be able to perform. Finally, having defined the maximum displacement values, it was observed the need to create more than one device model to meet the different stages of opening the hand until the opening of the fingers is complete.
Design and analysis: pneumatic drive device for hand movements recovery
Keywords: Elementos finitos; Dispositivo; Material hiperelástico; ENGENHARIAS::ENGENHARIA MECANICA::PROJETOS DE MAQUINAS; ENGENHARIAS::ENGENHARIA BIOMEDICA::ENGENHARIA MEDICA::INSTRUMENTACAO ODONTOLOGICA E MEDICO-HOSPITALAR